Impacts of Land Cover Changes on Land Surface Temperature using Landsat Imagery with the Supervised Classification Method - Astrid Damayanti; Farisya Isnaayu Khairunisa; Kintan Maulidina (Aceh International Journal of Science and Technology, 2023)
Land cover changes occur along with development and an increase in urbanization, affecting the region's ecology. Tarogong Kidul Sub-district, Garut District, experiences land cover changes that change land surface temperature. This study aims to determine the relationship between land cover changes and land surface temperature. This study uses Landsat 8 Surface Reflectance Tier 1 satellite imagery to extract Normalized Difference Vegetation Index information and process soil surface temperatures for three periods, 2014, 2017, and 2020 as well as supervised classification methods. Image collection and processing are done via Google Earth Engine and ArcGIS Pro software. The results were in the form of the distribution of land surface temperature correlated with changes in the value of the land cover vegetation index using simple linear regression and spatial correlation analysis. This study reveals that land cover change is closely related to the increase in land surface temperature indicated by the rise in land surface temperature in areas experiencing changes in land use. The results of linear regression analysis (84.49%) confirm that land cover changes and the greenness index of vegetation are the most critical driving factors for changes in land surface temperature.